Modelagem do planejamento agregado da produção em usinas cooperadas do setor sucroenergético utilizando programação matemática e otimização robusta - Paiva, Rafael Piatti Oiticica de (Universidade Federal de São Carlos, 2009)
The main concern of this work is related to the development of an aggregate production planning model of a cooperative society of sugar and alcohol milling companies. This mathematical model is based on a hierarquical approach between the annual planning problem of the cooperative and the tactical planning horizon of the sugarcane mills. In the cooperative level the main questions are related to the allocation of production goals to each mill and the management of inventory and dynamic demands. In the milling companies level a process selection model aims at helping the decision makers to determine the quantity of sugarcane crushed, the selection of sugarcane suppliers, the selection of sugarcane transport system suppliers, the selection of industrial process used in the sugar, alcohol, molasses and energy production. Besides that, this work presents an analysis of the impact of uncertainties in the aggregate planning problem parameters, using robust optimization techniques. To solve the linear and mixed integer mathematical problem found in this modeling, we applied a state of the art modelling language with an optimization solver. A case study was developed in a cooperative of sugar and alcohol milling companies located in the state of Alagoas- Brazil and at Santa Clotilde mill, located in the city of Rio Largo-AL. The results of this case study helped us to verify the applicability of the proposed models in the aggregate production planning of the studied organizations. Computational results are presented and analyzed with real data application.
Keywords: Planejamento da produção; Agroindústria sucroalcooleira; Programação inteira mista; Otimização robusta; Programação estocástica; Planejamento agregado de safra; Setor sucroenergético; Aggregate production planning; Mixed integer linear optimization; Robust optimization; Stochastic programming; Sugarcane mills; ENGENHARIAS::ENGENHARIA DE PRODUCAO